Inheritance of Bacillus thuringiensis Cry2Ab2 protein resistance in Helicoverpa zea (Lepidoptera: Noctuidae). Issue 11 (8th June 2020) - Yang, Fei; Head, Graham P; Price, Paula A; Santiago González, José C; Kerns, David L
Abstract: BACKGROUND: The corn earworm, Helicoverpa zea (Boddie), is a major target pest of pyramided Bt corn and cotton in the United States. Field‐evolved practical resistance to Cry1 and Cry2 proteins in H. zea has been documented in multiple locations in the United States. Understanding the genetic basis of Bt resistance is essential in developing insect resistance management (IRM) strategies for the sustainable use of the Bt crop technology. In this study, we characterized the genetic bases of Cry2Ab2 resistance in H. zea using diet‐overlay bioassays with two different forms of Cry2Ab2 protein. RESULTS: Laboratory bioassays using a Cry2Ab2‐resistant (RR) strain, a susceptible (SS) strain, as well as cross and backcross strains, revealed that resistance to Cry2Ab2 was autosomally inherited and controlled by more than one locus. In diet bioassays, the dominance of Cry2Ab2 resistance in H. zea varied from incompletely recessive to incompletely dominant across all tested Cry2Ab2 concentrations of either Bt corn leaf powder or solubilized protein. On leaf tissue of TwinLink cotton (expressing Cry1Ab and Cry2Ae), Cry2Ab2 resistance in H. zea was completely dominant. CONCLUSION: These results have significant implications for understanding the widespread field‐evolved resistance of H. zea against Cry1 and Cry2 proteins in Bt corn and cotton and should be useful in developing effective IRM strategies for H. zea. © 2020 Society of Chemical Industry Abstract : In this study, we characterized the genetic bases of Cry2Ab2 resistance in Helicoverpa zea (Boddie) using diet‐overlay bioassays with two different forms of Cry2Ab2 protein. © 2020 Society of Chemical Industry